Demographic Characteristics of Academic Advisors for Intercollegiate Athletics of NCAA D-I Member Institutions - Jackson, Jr., E. Newton; Quarterman, Jerome; Lyons, Robert; Yoo, Euidong (My University, 2001)
This investigation examined selected demographic factors of National Association of Academic Advisors for Atlhetics (N4A) professionals. A 23 item self-reported questionnaire was mailed in Spring 2001. A non-experimental descriptive exploratory design was implemented utilizing the field survey format. Research variables investigated were individual primary & secondary diversity characteristics. Primary diversity characteristics refer to human differences that are inborn and cannot be changed or modified during a person's life such as age, race, ethnicity, gender, physical abilities, and sexual orientation (Gardenswartz & Rowe, 1994). Secondary diversity characteristics are human differences that are inherited from the environment and can be changed or modified during a person's life such as educational level, work experience, income, marital status, religious beliefs, geographical location, parental status, behavioral style, etc. (Loden & Rosener, 1991). The responses from 213 questionnaires were coded and included in the SPSS computer analysis. Not all participants responded to all items; as a result, the sample sub-totals varied from 202-213. Results indicated 2/3 (67.4%) of advisors were likely to be 39 years or less in age and 113 (32.6%) were 40 years or older. Cross-tabulations implied male and female advisors were likely to have earned degrees at the same levels. White females were more often employed as academic athletic advisors in NCAA D-1 institutions than male or females of other ethnic minority groups collectively. Gender results from 212 responses indicated 83 (39.3%) were males and 129 (60.7%) were females. The average age of the respondents was 36.9 years and they ranged in age from 23 to 66 years (median age 34; mode age 29). Annual mean salaries of the advisors were $40,956 and ranged from $18,000 to $96,000 (median salary $39,000, mode $30,000). The average salary for the male advisors was 8.45% or $6,804 higher han the average salary for the female advisors. A similar trend was also shown for salary. The median salary for male advisors was $42,000 and $36,000 for female advisors. The difference in salary depicted an 8.57% or $6,000 increase for the males than females
Keywords: academic support; demographics; salary; sex/gender